Ongoing invasions by American bullfrogs and red-eared sliders in the Republic of Korea - Desiree Andersen; Amaël Borzée; Yikweon Jang (Animal Cells and Systems)
Invasive species can be unpredictable in their ability to adapt and spread across novel landscapes. American bullfrogs (Lithobates catesbeianus) and red-eared sliders (Trachemys scripta elegans) have become invasive in South Korea since their introduction in the 1970s through the food and pet trades. One of the first steps to their population regulations is to determine each species’ distribution in the country, which will allow for the identification of at-risk areas. In this study, we used a combination of kernel density and habitat suitability modeling to identify regions of current invasion and future spread for both species. We additionally modeled habitat suitability under a variety of climate scenarios, spanning 2021–2100 in order to determine possible climate change-based spread. For L. catesbeianus we found the total possible invasible area to be 46.2% of the country under current climate conditions, with 26.5% of the country currently invaded. For T. scripta, we found the total possible invasible area to be 38.5% of the country under current climate conditions, with 2.1% currently invaded. Finally, based on climate change predictions, both species are expected to have a decreased range of suitable area in the coming decades. The variations between the two invasive species pertain to their different breeding ecology.